A contemporary systematic review on liver transplantation for unresectable liver metastases of colorectal cancer. Issue 12 (14th March 2022) - Lebeck Lee, Cody M.; Ziogas, Ioannis A.; Agarwal, Rajiv; Alexopoulos, Sophoclis P.; Ciombor, Kristen K.; Matsuoka, Lea K.; Brown, Daniel B.; Eng, Cathy
Abstract : The 5‐year overall survival rate of a patient with unresectable metastatic colorectal cancer is poor at approximately 14%. Similarly, historical data on liver transplantation (LT) in those with colorectal liver metastases (CRLM) showed poor outcomes, with 5‐year survival rates between 12% and 21%. More recently, limited data have shown improved outcomes in select patients with 5‐year overall survival rates of approximately 60%. Despite these reported survival improvements, there is no significant improvement in disease‐free survival. Given the uncertain benefit with this therapeutic approach and a renewed investigational interest, we aimed to conduct a contemporary systematic review on LT for CRLM. A systematic review of the literature was performed according to the preferred reporting items for systematic reviews and meta‐analysis statement. English articles reporting on data regarding LT for CRLM were identified through the MEDLINE (via PubMed), Cochrane Library, and ClinicalTrials.gov databases (last search date: December 16th, 2021) by 2 researchers independently. A total of 58 studies (45 published and 13 ongoing) were included. Although early retrospective studies suggest the possibility that some carefully selected patients may benefit from LT, there is minimal prospective data on the topic and LT remains exploratory in the setting of CRLM. Additionally, several other challenges, such as the limited availability of deceased donor organs and defining appropriate selection criteria, remain when considering the implementation of LT for these patients. Further evidence from ongoing prospective trials is needed to determine if and to what extent there is a role for LT in patients with surgically unresectable CRLM. Abstract : In a small sample of recent data evaluating liver transplantation in patients with unresectable colorectal liver metastases, limited disease‐free survival and improved overall survival is noted in a few highly selected patients. Given the current available data, liver transplantation for unresectable colorectal liver metastases remains exploratory.